Les hétérosexuel·les et leurs ami·es gai·es : enquête sur la sociabilité gay-friendly dans les quartiers gentrifiés - Sylvie Tissot (Genre, Sexualité et Société)
This article is a sociological study of friendships that heterosexuals develop with gays and lesbians. Based on fieldwork in New York and Paris, it argues that these selective and controlled links provide social and moral valorization to upper-middle-class heterosexuals living in gentrified neighborhoods. At the same time, these friendships socialize these residents to gay-friendliness, especially during their youth. Further, when they go hand in hand with less conventional lives and with a distance from certain conjugal and sexual norms, these friendships may contribute to subverting hetero-normativity, primarily for straight women. Thus, gay-friendly friendships do not only reflect a growing acceptance of homosexuality; they reveal the social conditions of this acceptance, and shed light on the ambivalent reappropriation of the cause of gays and lesbians.